Unmeasured improvement work: the lack of routinely collected, service-related data in NHS endoscopy units in England involved in "modernisation" - Hutchings Hayley A; Thorne Kymberley; Elwyn Glyn (BMC Health Services Research, 2008)
Abstract Background The availability of routinely collected service-related endoscopy data from NHS endoscopy units has never been quantified. Methods This retrospective observational study asked 19 endoscopy units to submit copies of all in-house, service-related endoscopy data that had been routinely collected by the unit – Referral numbers, Activity, Number of patients waiting and Number of lost slots. Nine of the endoscopy units had previously participated in the Modernising Endoscopy Services (MES) project during 2003 to redesign their endoscopy services. These MES sites had access to additional funding and data collection software. The other ten (Control sites) had modernised independently. All data was requested in two phases and corresponded to eight specific time points between January 2003 and April 2006. Results Only eight of 19 endoscopy units submitted routinely collected, service-related data. Another site's data was collected specifically for the study. A further two units claimed to routinely collect service-related data but did not submit any to the study. The remaining eight did not collect any service-related endoscopy data routinely and liaised with their Trust for data. Of the eight sites submitting service-related data, only three were MES project sites. Of these three, the data variables collected were limited and none collected the complete set of endoscopy data variables requested. Of the other five sites, two collected all four endoscopy data types. Data for the three MES project sites went back as far as January 2003, whilst the five Control sites were only able to submit data from December 2003 onwards. Conclusion There was a lack of service-related endoscopy data routinely collected by the study sites, especially those who had participated in the MES project. Without this data, NHS endoscopy services cannot have a true understanding of their services, cannot identify problems and cannot measure the impact of any changes. With the increasing pressures placed on NHS endoscopy services, the need to effectively inform redesign plans is paramount. We recommend the compulsory collection of service-related endoscopy data by all NHS endoscopy units using a standardised format with rigorous guidelines.